Hubungan antara iklim keselamatan dengan gelagat keselamatan di dalam makmal dalam kalangan pelajar Universiti awam - Khairul Hafezad, Abdullah (2018)
This study aims to examine the direct effect of safety climate and the mediation effect of safety motivation and safety knowledge on the laboratory safety behavior among students in the university. The quantitative survey using questionnaires was used in this study. A total of 278 chemical or chemistry-based engineering students at three public universities from USM, UiTM and UniMAP were involved in this study. Data were analyzed using descriptive and inferential statistics via IBM SPSS Statistics and SEM SmartPLS 3.0. From the study, management commitment, supervisor commitment, student commitment, risk perception and safety reward were able to form safety climate construct. Meanwhile, safety compliance and safety participation were able to form laboratory safety behavior construct. This study verified that safety climate exerted direct effect on the laboratory safety behavior. In addition, safety motivation and safety knowledge exerted mediation effect on the relationship between safety climate and laboratory safety behavior among students in the university. In this study, the effect of mediation of safety knowledge contributes more compared to the safety motivation and the direct effect. Safety knowledge was the important element to manage laboratory safety in the university. Thus, the management of the university should consider the importance to offer subjects relating to occupational safety in the program that operate laboratory facilities in the university. For the reason, this study has verified that safety subject might boost and reinforce safety knowledge and bring favorable implications for laboratory safety behavior among students in the university. Hence, the study of the relationship between safety climate and laboratory safety behavior should be discovered in other educational organizations such as private higher learning institutions (IPTS), teacher education institutes (IPG), polytechnics and community colleges.